2013
DOI: 10.1210/jc.2012-3910
|View full text |Cite
|
Sign up to set email alerts
|

Recurrences of ACTH-Secreting Adenomas After Pituitary Adenomectomy Can Be Accurately Predicted by Perioperative Measurements of Plasma ACTH Levels

Abstract: Despite profound hypocortisolemia after adenomectomy, a simultaneously measured plasma ACTH level of >20 ng/L in the perioperative period is highly predictive of future recurrence of ACTH-secreting adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…Some previous studies [11, 14, 45, 46] demonstrated that patients with higher postoperative ACTH levels faced a higher risk of recurrence, which were consistent with our results. Given the short half-life of ACTH in the circulation, a low postoperative ACTH level might indicate that the ACTH-secreting adenoma was completely excised, therefore the recurrence rate was low.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Some previous studies [11, 14, 45, 46] demonstrated that patients with higher postoperative ACTH levels faced a higher risk of recurrence, which were consistent with our results. Given the short half-life of ACTH in the circulation, a low postoperative ACTH level might indicate that the ACTH-secreting adenoma was completely excised, therefore the recurrence rate was low.…”
Section: Discussionsupporting
confidence: 93%
“…Incorporating feature selection and univariate analysis, some results corroborated the previous studies, suggesting that younger age [43, 44], higher postoperative morning serum cortisol [6, 9-13], and higher postoperative morning ACTH [11, 14, 45, 46] had a detrimental effect on recurrence.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…23,27,32,37,52 Interestingly, subnormal serum ACTH is significantly less sensitive for sustained disease remission but also more specific for long-term disease remission than subnormal serum cortisol. 1,3,20,23,37 However, an ACTH value that may predict long-term recurrence has not been determined.…”
Section: Postoperative Acthmentioning
confidence: 99%